Analysis of the growth trajectories of junior residents in Japan: a longitudinal cohort study using data from a nationwide e-portfolio system (EPOC2) - Sachiko Ohde; Takahiro Kiuchi; Makoto Takahashi; MASANAGA YAMAWAKI; Tsuguya Fukui; Tsuyoshi Okuhara; Hiroko Okada; Nobutoshi Nawa; Eriko Okada; Ayako Kashimada; Yu Akaishi; Yujiro Tanaka (BMJ Open)
Objectives As more emphasis is placed on the acquisition of competencies in medical education, portfolios are increasingly being used for evaluation. EPOC2 (E-POrtfolio of Clinical training) is an e-portfolio system developed in Japan and is used by about 800 clinical training hospitals. The study objective is to identify the learning trajectory of junior residents to provide insights into the provision of better postgraduate and undergraduate medical education in Japan.Design Longitudinal cohort study.Setting Hospitals nationwide adopting EPOC2.Participants 7671 residents who participated in clinical training programmes at hospitals adopting EPOC2 between April 2020 and March 2022.Primary outcome measure Formative evaluation scores assessed through self-evaluation by junior residents and evaluations by supervisors/senior physicians at the end of each rotation in each clinical department.Results For all evaluation items, growth trajectories were divided into six groups, each with distinct characteristics based on the specific content of the evaluation form. For example, in the self-evaluation of medical knowledge and problem-solving (B-2), a lower percentage of respondents had adequate scores at the beginning of their training compared with other similar items. Compared with the self-evaluations of the other item groups (ie, forms A1–A4 and B1–B9), the self-evaluation of the item group related to seeing patients (ie, forms C1–C4) differed by showing a group that remained at or below 2 until the end, accounting for 2.8% to 7.0%, possibly indicating the relatively low confidence of the residents for these items.Conclusions Growth trajectories fall into six groups, each with its own characteristics depending on the content of the items. These findings offer valuable insights into the developmental trajectories of junior residents and may highlight opportunities for enhancing their training programmes in Japan. This underscores the usefulness of a nationwide evaluation system, enabling researchers to analyse clinical education outcomes across the country using uniform indicators.